Development of Learning Media for the Introduction of National Heroes Based on Virtual Reality in Class VI in Elementary School - Achmad Buchori; Muhammad Abdul Aziz; Theodora Indriati Wardani (MIMBAR PGSD Undiksha, 2025)
Students’ interest and motivation in learning about national heroes remain relatively low due to the lack of interactive and meaningful learning media. This study aims to explore and examine the feasibility of Virtual Reality (VR)-based learning media for introducing national heroes to elementary school students and evaluate its impact on learning motivation and learning experience. This research employed the ADDIE development model, including needs analysis, design, development, implementation, and evaluation. The subjects were elementary school students involved as users during limited and broader product trials. Data were collected through observations, interviews, and questionnaires, using expert validation sheets, observation sheets, and student response questionnaires as instruments. Quantitative descriptive analysis was conducted to determine media feasibility, while qualitative descriptive analysis was used to examine student responses and learning experiences. The results show that media and material experts rated the VR media as highly feasible, and students demonstrated highly positive responses, reflected in increased interest, active engagement, and more concrete understanding of historical information. It can be concluded that VR is practically effective as an innovative learning solution for abstract and historical content. Theoretically, these findings reinforce the application of technology-enhanced experiential learning in elementary education. Practically, the study implies that teachers should integrate immersive VR technology into learning to align with digital era demands and enhance students’ meaningful learning experiences.